2017
DOI: 10.15417/618
|View full text |Cite
|
Sign up to set email alerts
|

Reemplazo Total de Rodilla en pacientes menores de 55 años de edad con gonartrosis Seguimiento de 2 a 13 años. [Total Knee Arthroplasty for gonarthrosis in patients 55 years old or younger. 2-13 years follow-up.]

Abstract: <p><strong>Introducción</strong></p><p><strong></strong>El número de reemplazos totales de rodilla (RTR) en pacientes jóvenes continua en aumento. La literatura muestra resultados contradictorios y la mayoría incluyen pacientes con Artritis Reumatoide (AR). El propósito de este estudio fue analizar un grupo de RTR en menores de 55 años, excluyendo pacientes con AR, evaluando la sobrevida protésica, las fallas radiológicas y sus resultados funcionales.</p><p>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Scores were available for two instruments which are not strictly patient-reported outcome measures, although they each have a patient-reported component-the KSS, and the Hospital for Special Surgery (HSS) knee score. Improvements in the KSS exceeded the MCID; for the HSS, the MCID has not been established [33,36,37,39,41]. These results support the effectiveness of TKR in relieving pain and improving function for patients <65 years of age with osteoarthritis.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Scores were available for two instruments which are not strictly patient-reported outcome measures, although they each have a patient-reported component-the KSS, and the Hospital for Special Surgery (HSS) knee score. Improvements in the KSS exceeded the MCID; for the HSS, the MCID has not been established [33,36,37,39,41]. These results support the effectiveness of TKR in relieving pain and improving function for patients <65 years of age with osteoarthritis.…”
Section: Discussionmentioning
confidence: 72%
“…Large improvements were also attained in the function subscale. Studies which did not contribute to the meta-analysis reported comparable post-operative scores or improvements over follow-up periods ranging from 6.5 to 16.8 years for patients <55 years of age [36,39]. Scores were available for two instruments which are not strictly patient-reported outcome measures, although they each have a patient-reported component-the KSS, and the Hospital for Special Surgery (HSS) knee score.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations